Gomisin A Suppresses Colorectal Lung Metastasis by Inducing AMPK/p38-Mediated Apoptosis and Decreasing Metastatic Abilities of Colorectal Cancer Cells - Kee, Ji-Ye; Han, Yo-Han; Mun, Jeong-Geon; Park, Seong-Hwan; Jeon, Hee D.; Hong, Seung-Heon (Frontiers in Pharmacology, 2018)
Gomisin A (G.A) is a dietary lignan compound from Schisandra chinensis. In this study, the effect of G.A on the proliferation and metastasis of colorectal cancer (CRC) cells was investigated using several CRC cell lines and a lung metastasis mouse model. Both oral and intraperitoneal administration of G.A (50 mg/kg) inhibited lung metastasis of CT26 cells. Various concentrations of G.A were incubated with CRC cell lines and their viability was determined using a cell counting kit (CCK)-8 assay. G.A significantly decreased the viability of various CRC cell lines, whereas it did not change the proliferation of normal colon cells. G.A induced G0/G1 phase arrest and apoptosis of CT26 and HT29 cells by regulating cyclin D1/cyclin-dependent kinase 4 (CDK4) expression and apoptotic proteins such as caspases and B-cell lymphoma-2 (Bcl-2) family proteins, respectively. G.A-induced apoptosis was mediated by AMPK/p38 activation in CRC cells. A non-cytotoxic concentration of G.A inhibited epithelial-mesenchymal transition (EMT) of CRC cells by modulating E-cadherin and N-cadherin expression levels. Moreover, the migration and invasion of CRC cells were reduced by G.A treatment. Especially, G.A decreased matrix metalloproteinase (MMP)-2 and MMP-9 expressions and activities. G.A ameliorated lung metastasis of CRC cells by decreasing cell survival and metastatic abilities of CRC cells. Thus, G.A might be a potential novel therapeutic agent for metastatic CRC.